Psychosomatic Aspect of the COVID-19 Pandemic - Rahmy Nurdin; Arina Widya Murni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
A pandemic is an epidemic of an infectious disease that spreads over a wider area, multiple continents, or the entire world at the same time. Since COVID-19 was declared a pandemic on March 11th, 2020, the world has entered a global emergency phase. The COVID-19 pandemic has changed the way of life and become a stressor in this century. Various factors become stressors during a pandemic. Many people experience negative emotions, such as fear, anxiety, and depression, during the COVID-19 pandemic. When negative emotions are no longer controlled, they will have a negative effect on the autonomic nervous system and cerebral cortex, causing psychosomatic and somatic symptoms. Many studies have shown a significant relationship between perceived stress and psychosomatic complaints. Research has also shown that stress during the COVID-19 pandemic is associated with an increase in psychosomatic symptoms. In the future, negative emotions during a pandemic, if not managed properly, can lead to post-traumatic stress disorder (PTSD). Peoples who are vulnerable to mental disorders due to COVID-19 include people with chronic diseases. Stressors during a pandemic can exacerbate anxiety, depression, and chronic stress in people with chronic diseases, causing exacerbations of chronic diseases, increasing somatic symptoms, and decreasing immune responses, resulting in increased infection and mortality risk.